Uterine sarcomas – an evaluation of treatment results and prognostic factors - Karolewski, Kazimierz; Gliński, Bogdan; Jakubowicz, Jerzy; Blecharz, Paweł; Ryś, Janusz; Bieda, Tomasz; Urbański, Krzysztof (Archives of Medical Science, 2009)
Introduction: The objective of this study was to evaluate the efficacy of surgery plus adjuvant radiotherapy in 98 uterine sarcoma (US) patients and to analyse reasons for treatment failure and the prognostic factors in those patients. Material and methods: Between 1980 and 2000, 98 patients with uterine sarcoma were treated with surgery followed by postoperative radiotherapy. This group consisted of 70 patients with leiomyosarcoma (LMS) and 28 patients with endometrial stromal sarcoma (ESS). Results: Five-year survival rate with no evidence of disease (NED) was 49% for 98 US patients. In the ESS subgroup, 5 year survival rate with NED was 75% and in the LMS subgroup only 38.6%. Analysis of the outcomes based on stage of disease revealed that in the early stage group (FIGO stages I and II) 60.8% of US patients survived for 5 years with NED, whereas in locally advanced stages (stages III, IVA) only 12.5% survived for 5 years with NED. In the LMS subgroup the dominant reason for treatment failure was distant metastases, while in the ESS subgroup, there were locoregional recurrences. Conclusions: Combined surgery plus radiotherapy was a relatively effective therapy only in the treatment of early stage US (stages I and II). Independent prognostic factors in this group of patients were stage and microscopic type of sarcoma. The basic reason for failure of combined treatment in the group of LMS patients was the spread of malignancy, while in ESS patients it was regional recurrence.